Avian influenza H9N2 subtype in Ghana: virus characterization and evidence of co-infection. Issue 5 (3rd September 2019) - Awuni, Joseph A.; Bianco, Alice; Dogbey, Otilia J.; Fusaro, Alice; Yingar, Daniel T.; Salviato, Annalisa; Ababio, Patrick T.; Milani, Adelaide; Bonfante, Francesco; Monne, Isabella
ABSTRACT: Between November 2017 and February 2018, Ghanaian poultry producers reported to animal health authorities a dramatic increase in mortality rate and a relevant drop in egg production in several layer hen farms. Laboratory investigations revealed that the farms had been infected by the H9N2 influenza subtype. Virological and molecular characterization of the viruses identified in Ghana is described here for the first time. Whole genome analysis showed that the viruses belong to the G1-lineage and cluster with viruses identified in North and West Africa. The low pathogenicity of the virus was confirmed by the intravenous pathogenicity index assay. Further investigations revealed co-infection with infectious bronchitis virus of the GI-19 lineage, which very likely explained the severity of the disease observed during the outbreaks. The H9N2 outbreaks in Ghana highlight the importance of performing a differential diagnosis and an in-depth characterization of emerging viruses. In addition, the detection of a potentially zoonotic subtype, such as the H9N2, in a region where highly pathogenic avian influenza H5Nx is currently circulating highlights the urgency of implementing enhanced monitoring strategies and supporting improved investments in regional diagnostic technologies. RESEARCH HIGHLIGHTS Influenza A H9N2 subtype was detected in layer hens in Ghana in 2017–2018 Whole genome characterization of seven H9N2 viruses was performed Phylogenetic trees revealed that the H9N2 viruses belong to the G1 lineage The HA protein possesses the amino acid mutations 226L and 155T Co-infection with infectious bronchitis virus of the GI-19 lineage was identified